TANTANGAN PEMBANGUNAN BERKELANJUTAN DI ERA OTONOMI DAERAH - Lestario Widodo (BPPT)
Regional outonomy that is meant as right, authority and obligatory of the district (kabupaten/kota) to regulateand manage their own governance and community’s interests gave pressure impacts to the environmentalsustainability since its implementation in 2001. The spirit to utilize natural resources from the districtarea tend to explore the environment irresponsibly which resulted in degradation of the environmentalsustainability. The district policies had often not been assessed in detail before implementation especiallytheir impacts to the environment. This caused the regional autonomy went into a different direction,therefore it needs an improvement in the level of program determination, policy and regulation applied, sothat the spirit to conduct decentralised governance will be kept on the rules of sustainable developmentwhich is environmentally friendly.Key words : Sustainable Development, Regional Autonomy